Corporate social responsibility spending of commercial banks: determinants and consequence - Alhassan Musah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The contribution of firms towards society in the form of corporate social responsibility has attracted significant concern for many stakeholders, especially among banks in Ghana. It is perceived that; banks especially do Corporate Social Responsibility just because they are the most profitable sector in Ghana. The study sort to examine the kind of relationship that exists between bank performance and CSR in Ghana. Also, to determine how bank size and profitability and it's listing status and foreign ownership influence CSR spending in Ghana. The study sampled 24 commercial banks over seven years from 2010 to 2016. The study analyzed data using statistical tools such as descriptive statistics, correlation analysis, and panel regression analysis. The study found out that engaging in CSR activities increases banks' profitability in Ghana, especially for ROE. Besides, the study concluded that bigger and larger banks are more profitable than small companies, so they are more involved in CSR activities. The study also investigated whether foreign ownership and the listing status of banks influence CSR spending. On this aspect, the study found out that banks' listing status influences CSR spending, but foreign ownership does not. The result implies that listed banks are more public and faces more social pressure hence they spend more on CSR to legitimize their operations.